The connection between corporate social responsibility and corporate respect for human rights - Ana Čertanec (DANUBE: Law, Economics and Social Issues Review, 2019)
The purpose of this article is to study the connection between corporate respect for human rights and corporate social responsibility. The author argues that business entities have a responsibility to respect human rights and that this responsibility forms part of their corporate social responsibility. The author defends the view that business and human rights issues are distinct from corporate social responsibility issues in their legal nature and content, while the strategic approach in the implementation of these concepts is the same. The author further examines whether voluntary corporate social responsibility initiatives include human rights, and how society understands the connection between the two. The conclusions of the article shed light on the interconnection between these two terms.
Keywords: 330; Business and Human Rights; Corporate Respect for Human Rights; Corporate Social Responsibility; CSR Initiatives; Human Rights